A ‘Right’ to the university - van Marle, Karin (Acta Academica: Critical views on society, culture and politics, 2019)
I consider to what extent, if at all, rights – or to take it wider, law – can contribute or even respond to what is referred to as the ‘current crisis’ in higher education. To what extent does rights discourse still enable radical political claims that could engage with the complexity of the moment and support a politics of resistance? I recall arguments on the limits of law, in particular the inability of law to be self-reflexive, and also some critical responses to rights as such. Could these critical responses disclose possibilities for a radically different conception of right, of a ‘Right’ – particularly the Right to the university – that emerges from a place of anxiety, disruption and ‘unselfing’ rather than preservation? What could be at stake in thinking about a ‘Right’ to the university against the background of the notion of the Right to the city? The potential relevance of the Right to the city, linked to the notion of ‘inhabitance’, is that it challenges the modern, technical and functional notion of ‘habitat’. Habitat is devoid of any notion of politics, most pertinently political resistance. A contemplation of a Right to the university will have to have at its core the notion of ‘inhabitance’ that will resonate with Lefebvre’s notion of “lived space”.